Sexual Violence and Development Implications in Uganda Universities: The Case of Kyambogo University - Lubaale, Grace; Kebirungi, Harriet; Ejuu, Godfrey (Tanzania Journal of Development Studies, 2023)
Sexual violence (SV) remains a menace in society, a stonewall hindering the coexistence and holistic growth of all genders. It is a challenge in higher education despite the fact that relevant legal and policy frameworks intended to curtail its prevalence exist. The unwinding subsistence of SV forms the basis of this study, which specifically aims to establish its nature, causes, development implications, and the way forward for the Kyambogo University (KyU). This study was qualitative in nature, and adopted a case research design in which SV phenomenon as a lived experience was studied, described and interpreted from the victim’s point of view. Qualitative data derived from an interview guide was processed with the help of content analysis tools, while observing standard ethical considerations. Results indicate that sexual violence takes the form of sexual harassment, sexual exploitation, intimate partner sexual assault, unwanted sexual contacts, rape, showing ones genitals, masturbation and peeping at people in private sexual acts. The causes are male chauvinism, poverty, difficulty to secure evidence, corruption and stigmatization; all of which have resulted into far-reaching negative effects on the health, education achievement, research and innovations, returns on higher education and self-esteem of the victims, and the institution as a whole. Conclusively, therefore, SV is a reality in KyU, perpetuated largely by the male gender. Since it is socially constructed, it can be deconstructed. Thus, the study recommends awareness creation, enacting more stringent gender and anti-SV policies, gender responsive budgeting, plus monitoring and evaluation of every step in the SV direction so as to end this vice.
Keywords: Sexual Violence; Uganda Universities; Kyambogo University